2022
DOI: 10.3390/resources11010005
|View full text |Cite
|
Sign up to set email alerts
|

From Old Habits to New Routines—A Case Study of Food Waste Generation and Reduction in Four Swedish Schools

Abstract: Public food service organizations are large producers of food waste, which leads to greenhouse gas emissions and the waste of natural resources. The aim of the present article was to gain insight into reasons for food waste and possible solutions for lowering food waste in schools in Sweden. In order to do so, food waste quantification in school canteens in two Swedish municipalities and nine qualitative interviews with key actors were conducted. Both municipalities displayed a high degree of variation in food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…These findings are comparable to a study at four Swedish schools that found serving waste, followed by plate waste were the largest food waste contributors. (Persson Osowski et al ., 2022) In addition to the excessive food waste and the resources that go into that waste, it is estimated that $5.43 per resident from the government-mandated food and beverage budget is wasted on food that is purchased solely to be thrown away at lunch and dinner. The study did not include potential waste from the breakfast meal period or two “snack times” which would most likely increase the total food waste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are comparable to a study at four Swedish schools that found serving waste, followed by plate waste were the largest food waste contributors. (Persson Osowski et al ., 2022) In addition to the excessive food waste and the resources that go into that waste, it is estimated that $5.43 per resident from the government-mandated food and beverage budget is wasted on food that is purchased solely to be thrown away at lunch and dinner. The study did not include potential waste from the breakfast meal period or two “snack times” which would most likely increase the total food waste.…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory studies are often used when a lack of research in a field exists and are typically theory-informed versus theory-driven (Waters, 2007; Mainardes et al ., 2010; Elman et al ., 2020). Similar mixed-method approaches have been used recently in the study of food waste in other foodservice operations (Persson Osowski et al ., 2022; Silvennoinen et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…FW at the consumption stage of the food supply chain could also be categorized according to when the waste occurs. For example, FW produced during the purchase and storage of food is considered to be "spoilage food waste" (or "storage waste" [13]); "preparation food waste" occurs during cooking, i.e., due to peeling, cutting, as well as overproduction or food surplus; "leftover waste" occurs when the prepared food is not served to the consumer (unserved food); "plate waste" pertains to the food served to the consumer but not eaten [14].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In Mexico, there are precedents on studies of generation, recycling and final disposal of municipal solid waste [23,24], or studies on waste generation and management under a circular economy approach [25,26] including proposals for models to forecast waste generation [27], however, none focus on polystyrene waste, but are studies of residues in general. In the international context, there are reported works on studies of generation and quantification of waste at the domestic level and in cities without a specific quantification for polystyrene waste [28][29][30][31]. It is worth mentioning that the studies on waste generation that had the most boom in the last two years were those related to the generation of hospital waste because of the COVID -19 pandemic [32][33][34].…”
Section: Introductionmentioning
confidence: 99%